Corneal Confocal Microscopy Detects Neuropathy in Subjects With Impaired Glucose Tolerance - Asghar, Omar; Petropoulos, Ioannis N.; Alam, Uazman; Jones, Wendy; Jeziorska, Maria; Marshall, Andrew; Ponirakis, Georgios; Fadavi, Hassan; Boulton, Andrew J.M.; Tavakoli, Mitra; Malik, Rayaz A. (Diabetes care, 2014)
Impaired glucose tolerance (IGT) represents one of the earliest stages of glucose dysregulation and is associated with macrovascular disease, retinopathy, and microalbuminuria, but whether IGT causes neuropathy is unclear. Thirty-seven subjects with IGT and 20 age-matched control subjects underwent a comprehensive evaluation of neuropathy by assessing symptoms, neurological deficits, nerve conduction studies, quantitative sensory testing, heart rate variability deep breathing (HRVdb), skin biopsy, and corneal confocal microscopy (CCM). Subjects with IGT had a significantly increased neuropathy symptom profile (P < 0.001), McGill pain index (P < 0.001), neuropathy disability score (P = 0.001), vibration perception threshold (P = 0.002), warm threshold (P = 0.006), and cool threshold (P = 0.03), with a reduction in intraepidermal nerve fiber density (P = 0.03), corneal nerve fiber density (P < 0.001), corneal nerve branch density (P = 0.002), and corneal nerve fiber length (P = 0.05). No significant difference was found in sensory and motor nerve amplitude and conduction velocity or HRVdb. Subjects with IGT have evidence of neuropathy, particularly small-fiber damage, which can be detected using skin biopsy and CCM.